1996
DOI: 10.1021/jp951779f
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Upper Bounds on Interfacial Charge-Transfer Rate Constants between Semiconducting Solids and Outer-Sphere Redox Couples

Abstract: Theoretical expressions for the charge-transfer rate constant at a semiconductor/liquid junction have been modified to include the effects of adiabaticity and the existence of a Helmholtz layer at the solid/liquid interface. These expressions have yielded an estimate of the maximum interfacial charge-transfer rate constant, at optimal exoergicity, for a semiconductor in contact with a random distribution of nonadsorbing, outer-sphere redox species. An experimental upper bound on this interfacial charge-transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
119
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(132 citation statements)
references
References 75 publications
13
119
0
Order By: Relevance
“…The Si/liquid contacts that showed a low effective S value as probed by photoconductivity decay measurements also formed an inversion layer in contact with the electrolyte solutions. Although the near-surface channel conductance experiments reported herein were performed using ͑100͒-oriented Si surfaces, the flatband potentials of ͑100͒-and ͑111͒-oriented Si surfaces are sufficiently similar 11 that the general conclusions derived from these measurements regarding the electrochemical potentials of the electrolyte solutions required to form an inversion layer are expected to be applicable, with only minor changes, to ͑111͒-oriented Si surfaces.…”
mentioning
confidence: 82%
“…The Si/liquid contacts that showed a low effective S value as probed by photoconductivity decay measurements also formed an inversion layer in contact with the electrolyte solutions. Although the near-surface channel conductance experiments reported herein were performed using ͑100͒-oriented Si surfaces, the flatband potentials of ͑100͒-and ͑111͒-oriented Si surfaces are sufficiently similar 11 that the general conclusions derived from these measurements regarding the electrochemical potentials of the electrolyte solutions required to form an inversion layer are expected to be applicable, with only minor changes, to ͑111͒-oriented Si surfaces.…”
mentioning
confidence: 82%
“…This equation is based on the assumption that the capacitance of the space charge layer is much less than that of the Helmholtz layer and at high frequency (1 kHz), the contribution of Helmholtz capacitance to the measured electrode capacitance is negligible [62]. Thus the capacitance of the semiconductor/electrolyte interface mainly expresses the capacitance of the space charge layer of the semiconductor [63][64][65].…”
Section: Mott-schottky Plotmentioning
confidence: 99%
“…11 Redox couples that have very positive redox potentials are capable of extensive charge transfer from the Si into the electrolyte, thereby establishing an inversion layer at the surface of n-type Si. [12][13][14] Simulations of the surface recombina- tion rate using an extended Shockley-Read-Hall formalism, which incorporates the effects of band bending, have in fact shown that S decreases significantly with increases in positive charge at the surface of n-type Si. 11 Removal of the sample from the electrolyte will generally change the surface potential in a direction that reduces the band bending, so the observed value of S should increase and the variations in the surface trap density, N t , can then be reflected in the measurements of S under these conditions.…”
mentioning
confidence: 99%
“…[12][13][14] Near-surface channel conductance measurements in p ϩ -n-p ϩ Si structures exposed to electrolytes have clearly demonstrated the formation of an inversion layer at n-Si/CH 3 OH-5.4 mM Me 2 Fc-2.9 mM Me 2 Fc ϩ contacts but not at CH 3 OH-Me 10 Fc ϩ/0 electrolytes. 12 Mott-Schottky measurements of the n-Si/CH 3 OH-Me 2 Fc ϩ/0 contact have indicated an equilibrium barrier height of Ϸ1.03 V, [14][15][16] which is sufficient to drive the system into carrier inversion. The surface recombination velocity of Si/CH 3 OH contacts after treatment with CH 3 OH-Me 2 Fc ϩ/0 , deduced from current density versus potential data, is Ͻ100 cm s Ϫ1 , whereas higher S values were deduced for these Si samples in contact with redox systems such as CH 3 OH-Me 10 Fc ϩ/0 that cannot produce an inversion layer at the Si surface.…”
mentioning
confidence: 99%